Implementasi Metode Montessori Dalam Mengembangkan Sensori Motorik Untuk Meningkatkan Kemandirian Anak Usia 3 – 4 Tahun Di KB Babur Rahman Pakuniran - Alfir Rahmah, Alisyia; Fatimah, Nur; Adelita Febrianti P, Debby (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
Basically, children need meaningful activities, besides that, children like to participate in adult activities to make them feel needed and useful. This is an opportunity to grow a sense of independence in children. One of the tasks of early childhood development is to build independence, which needs to be developed from an early age. Montessori is one of many approaches that can be used to improve children's independence. In this approach, children are trained with Montessori props designed to improve children's senses, cognitive abilities, and independence. The purpose of this research is to find out how the Montessori Method forms an independent character in early childhood at KB Babur Rahman pakuniran. Principals, class teachers, and accompanying teachers are the main data sources. Reference books and journals related to the Montessori Method and child independence are the secondary data sources. Data is collected through observation, interview, and documentation. Research results show that the Montessori method is well used to build an independent character in early childhood at KB Babur Rahman Pakuniran, from planning and implementing learning to evaluation. It is very important for the child's environment to form their independent personality, especially the Montessori environment, which encourages children to be more independent. Children's ability to serve themselves is an example of the result of the Montessori method in building children's independent character.